2022
DOI: 10.1159/000522485
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Decreases Cytotoxicity and Mitigates Inflammatory and Oxidative Stress Responses in a Ferret Organotypic Brain Slice Model of Neonatal Hypoxia-Ischemia

Abstract: The gyrencephalic ferret brain is an excellent model in which to study hypoxia-ischemia (HI), a significant contributor to neurological injury in neonates. Vitamin E, an essential fat-soluble antioxidant, reduces oxidative stress and inflammation in both animal models and neonates. The aim of this study was to assess the effects of Vitamin E after oxygen glucose deprivation (OGD) in an organotypic ferret brain slice model of neonatal HI. We hypothesized that Vitamin E would decrease cytotoxicity, inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Preclinical studies to date have largely used various rodent in vitro and in vivo models of brain injury, where Vit E has been shown to decrease both inflammation and oxidative stress, with resulting neuroprotection [ 22 , 32 , 33 , 34 , 35 , 36 , 37 ]. These effects have been examined most frequently in the hippocampus and cerebellum, with fewer studies looking specifically at other regions such as the cortex and basal ganglia [ 7 , 38 , 39 ] ( Figure 2 ). For example, Vit E deficiency in rodents has been shown to result in axonal degeneration in the hippocampus [ 38 ].…”
Section: Neuroprotection In Preclinical Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preclinical studies to date have largely used various rodent in vitro and in vivo models of brain injury, where Vit E has been shown to decrease both inflammation and oxidative stress, with resulting neuroprotection [ 22 , 32 , 33 , 34 , 35 , 36 , 37 ]. These effects have been examined most frequently in the hippocampus and cerebellum, with fewer studies looking specifically at other regions such as the cortex and basal ganglia [ 7 , 38 , 39 ] ( Figure 2 ). For example, Vit E deficiency in rodents has been shown to result in axonal degeneration in the hippocampus [ 38 ].…”
Section: Neuroprotection In Preclinical Modelsmentioning
confidence: 99%
“…Studies have also shown that inhibition of GSH recycling with the Xc-inhibitor erastin results in uncontrolled lipid peroxidation, which can be either masked or rescued in part by Vit E [ 25 , 43 ]. In a ferret organotypic brain slice model, Vit E (25 IU/kg) administered after OGD decreased cytotoxicity and inhibited oxidative stress by maintaining higher levels of GSH, and decreased transcription of genes responsible for oxidative stress and inflammation [ 7 ]. Vit E is also thought to dampen microglia activation in both mice and rats via decreased production of proinflammatory nitric oxide (NO), IL-1α, TNF-α, and reduce the expression of inducible nitric oxide (iNOS), though this effect has predominately been described in the hippocampus [ 2 ].…”
Section: Neuroprotection In Preclinical Modelsmentioning
confidence: 99%
See 3 more Smart Citations